2021
DOI: 10.3390/agronomy11061225
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Response of Wheat-Chickpea Intercropping to Nitrogen Fertilization Using Agro-Ecological Competitive Indices under Contrasting Pedoclimatic Conditions

Abstract: Wheat–chickpea intercrops are not well studied, despite the importance of these two species in increasing agricultural profitability and ensuring nutritional and food security. The present study aims to assess the intercropping arable system’s services under contrasting field management and climate conditions. Simultaneously, this assessment focuses on the most agronomic and ecological indices widely used in the literature. Durum wheat (Triticum turgidum durum L.cv. VITRON) and chickpea (Cicer arietinum L.cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…An integrated crop protection system (ICPS) can be established taking into account the other agricultural practices [11], namely, the fertilization system, which is in a close relationship with the protection system [12], the crop rotation system, used as a natural barrier against a wide range of soil-borne fungal pathogens, the intercropping system, and plant breeding by developing new cultivars adapted both to the specific climatic conditions of the regions and to biotic stresses [13][14][15]. For example, according to Flower et al (2019) [16], fallow and lupin in the farmer rotation system are the most effective at reducing pathogens levels.…”
Section: Introductionmentioning
confidence: 99%
“…An integrated crop protection system (ICPS) can be established taking into account the other agricultural practices [11], namely, the fertilization system, which is in a close relationship with the protection system [12], the crop rotation system, used as a natural barrier against a wide range of soil-borne fungal pathogens, the intercropping system, and plant breeding by developing new cultivars adapted both to the specific climatic conditions of the regions and to biotic stresses [13][14][15]. For example, according to Flower et al (2019) [16], fallow and lupin in the farmer rotation system are the most effective at reducing pathogens levels.…”
Section: Introductionmentioning
confidence: 99%
“…At 56 and 70 DAS plant height of the chickpea was conspicuously lower in the N0, N30, and N60 compared to the N90 application rates. In later stages of growth (84DAS), significance in plant height between N90 and the other rates (N0, N30, and N60) reduced, mainly due to senescence (Kherif et al 2021). The final plant height after N30 to N90 fertilization gave taller plants indicating that increased N-application rates can positively increase plant growth of chickpea.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous types of intercropping systems have been practiced widely in many countries throughout the world, including wheat–maize [ 12 ], maize–fava bean [ 13 ], wheat–pea and maize–soybean [ 14 ], and legume–cereal [ 15 ]. In particular, cereal–legume is the most common type of intercrop cultivated worldwide and particularly in North African countries [ 16 , 17 ]. Several studies investigating the effect of cereal–legume intercrops on rhizosphere soil P behavior have indicated that the legume species can solubilize the organic soil P through root-induced processes, such as acidification of the rhizosphere soil following the exudation of organic acids, including malate and citrate, and/or indirectly through microbial activity [ 18 ], thereby enhancing the P availability for the intercropped species, such as durum wheat (Dw) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%